The Potency of NTHi lic1A Gene as a Biomarker in Determining The Severity of Post-Viral Acute Rhinosinusitis - Imam Megantara; Ronny Lesmana; Nova Sylviana; Sunarjati Soedigdoadi; Teti Madiadipoera (The Prodia Education and Research Institute (PERI), 2021)
BACKGROUND: The lic1A gene is an important virulence factor for non-typeable H. influenzae (NTHi), which allows its translocation from the nasopharynx into the sinonasal cavity and modulates more severe inflammatory processes. This study is aimed for identifying the potential correlation between the NTHi lic1A gene expressions and the severity of post-viral acute rhinosinusitis.METHODS: Sixty patients who were diagnosed with post-viral acute rhinosinusitis, were recruited from an ENT clinic in a referral hospital, in Bandung, West Java, Indonesia. All patients underwent a historical assessment and ENT examination. The nasal specimen was taken from the patient’s middle meatal. The NTHi lic1A gene expression was detected using Polymerase Chain Reaction (PCR).RESULTS: We observed that eight patients had the NTHi lic1A (+), with a strong correlation toward the dominant symptoms (nasal obstruction and discharge). In addition, the symptom’s duration of the NTHi lic1A (+) was twice longer than patients with the NTHi lic1A (-). Its severity was significantly more different between the two groups (p=0.034).CONCLUSION: Taken together, the presence of the NTHi lic1A gene is significantly associated with the severity of the disease and the symptom’s duration. Thus, the NTHi lic1A gene could potentially be a good marker for assessing the severity of post-viral acute rhinosinusitis cases in the future.KEYWORDS: H. influenzae, rhinosinusitis, nasal obstruction, virulence factors